2014
DOI: 10.1111/cpr.12123
|View full text |Cite
|
Sign up to set email alerts
|

Parmelia sulcata Taylor and Usnea filipendula Stirt induce apoptosis‐like cell death and DNA damage in cancer cells

Abstract: In this study, methanolic extracts of Parmelia sulcata and Usnea filipendula induced apoptosis-like cell death by causing DNA damage, to cancer cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 18 publications
(26 reference statements)
1
18
0
Order By: Relevance
“…There is two posible splanations for that question. First, that there is cytokeratin-18 in brain; and this has been found in a study of patients with pituitary adenomas [ 36 ], and in a study of rats with glioma [ 37 ]. In the study by Luiciani et al was found CCCK-18 in cell extracts of patients with pituitary adenomas, and the use of octreotide induced apoptosis in cells of growth hormone-secreting tumors assessed by the increased of CCCK-18 in cell extracts [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is two posible splanations for that question. First, that there is cytokeratin-18 in brain; and this has been found in a study of patients with pituitary adenomas [ 36 ], and in a study of rats with glioma [ 37 ]. In the study by Luiciani et al was found CCCK-18 in cell extracts of patients with pituitary adenomas, and the use of octreotide induced apoptosis in cells of growth hormone-secreting tumors assessed by the increased of CCCK-18 in cell extracts [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Luiciani et al was found CCCK-18 in cell extracts of patients with pituitary adenomas, and the use of octreotide induced apoptosis in cells of growth hormone-secreting tumors assessed by the increased of CCCK-18 in cell extracts [ 36 ]. In the study by Adri et al was found CCCK-18 in cell extracts of glioma from rats, and the use of Parmelia sulcata Taylor (one of the most common lichens that lives mainly in the bark of the trees) induced apoptosis in cell tumors assessed by the increased of CCCK-18 in cell extracts [ 37 ]. Second, that MMCAI may cause a systemic inflammatory response syndrome (SIRS), and this could activate sistemic cellular apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the lichen species induced apoptosis-like cell death by causing DNA damage to cancer cells (Ari et al, 2014a). The antigrowth effects of UFE may arise from its secondary metabolites.…”
Section: Cytotoxic Activities Of Ufe By the Mtt And Atp Assaysmentioning
confidence: 83%
“…Moreover, methanol extract of Lobothallia alphoplaca and Melanelia disjuncta exhibited high cytotoxicity against both cancer cell lines [99]. Additionally, treatment of A549, PC-3, Hep3B, and C6 cell lines with methanol extracts of Parmelia sulcata Taylor and Usnea filipendula Stirt led to the cytotoxic, genotoxic and apoptosis-inducing effects in all tested cell lines [100]. Another in vitro experiment of methanol extract of Hypogymnia physodes (low concentrations) indicated anticancer and/or apoptosis-inducing effects on MCF-7 and MDA-MB-231 cells and the genotoxic (high concentrations) impact on human lymphocytes [101].…”
Section: Determination Of Lichens' Extracts Effect Against Cancer Cellsmentioning
confidence: 91%